‘Making audible to one a roar of sound where others find perfect stillness’: Soundscape in George Eliot’s The Lifted Veil and the physiological acoustics - Lilia Miroshnychenko (Cahiers Victoriens et Edouardiens)
The article suggests how the ideas in physiological acoustics summed up and further developed by Hermann von Helmholtz, a German physicist, whose figure won popularity among Victorian intellectuals from the middle of the century, could be appropriate to George Eliot’s early writing. The resonant theory informs, in various ways, the soundscape of The Lifted Veil (1859), redefining the function of sound in the text—as a literary device, a means of characterisation, a narrative instrument, and what’s more—a component of the author’s moral imperative of sympathy.